PENGARUH PENDEKATAN BERMAIN TERHADAP KETERAMPILAN SEPAK SILA - Saputra, Andi; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the lack of soccer skills in the game of sepak takraw, showing that students' skills in doing soccer are less than optimal, lacking in soccer techniques. This study aims to learn how to learn the game of football in soccer extracurricular participants at SMA Negeri 1 Meliau. Research is an experimental study. The method used is "Pre-Experimental Design". The population and sample of this study were those who participated in the soccer takraw extracurricular at SMA Negeri 1 Meliau with a sampling technique that was purposive sampling from a total of 20 participants. The results of this study prove that there is a significant influence on Play Games. The results of the study obtained an average value of pretest with a value of 7.30 and posttest obtained an average value of 8.45. The percentage of importance in this study was 17.80%. Then it can be denied that there are suggested benefits of playing against soccer skills in the takraw extracurricular participants.Â Keywords: Approach to Play, Skills Sepak Sila, Sepak Takraw